The Banat Bulgarians – a Phenomenon of Cultural Continuity - Walczak-Mikołajczakowa, Mariola (Poznańskie Studia Slawistyczne, 2015)
Nowadays, the so-called Banat Bulgarians are a numerous group of the descendants of Bulgarian Catholics, which were forced to emigrate to Wallachia in the end of the 17th century and in the beginning of the 18th century and from there in years 1738–1741 to Banat. Small part of them (after 1878) returned to Bulgaria where they establish new villages. Most of them still live in Romanian territory, decidedly less numerous colonies are in Hungary and in Serbia. From the end of 19th century they were a subject of interest to historians and linguists. For historians, their history were extremely interesting. For linguists, because they managed to salvage the dialect which became (in the half of the 19th century) a base of literary norm that was to shape their language.